Analysis of the quality of diagnostic tests for COVID-19 in a city in the northwestern region of Sao Paulo - Marques, Geovana Caliente; de Lima, Heloísa Fusetto; Garcia, Lidyane Bortoleto; Telini, Wagner Moneda; Guimarães, Vera Lúcia Dorigão; Bofo, Daniele Cristina (Seven Editora, 2023)
In Brazil, the first cases of COVID-19, were diagnosed in February; on the 3rd of the same month, the country declared a Public Health Emergency of National Importance (ESPIN). The National Contingency Plan for COVID-19 was initiated, which in addition to the health measures, created TeleSUS. Given this scenario, the National Health Surveillance Agency (ANVISA), approves the expansion of testing. Most of the techniques used are: reverse transcriptase polymerase chain reaction (RT-PCR), loop-mediated isothermal amplification (LAMP), lateral flow technique, rapid individual test; and enzyme-linked immunosorbent assay (ELISA). According to the World Health Organization (WHO), the gold standard technique is from RT-PCR. Thus, this study aimed to analyze the quality of diagnostic tests in a city in the Northwestern region of the state of São Paulo. This was evaluated by means of a cross-sectional, observational and individual study, with simple random probabilistic sampling, with exclusion criteria for deaths and people with incomplete data in the list. It was analyzed, 215 residents, hospitalized, who performed the standard other test (RT-PCR) and TR, between June/2020-June/2021, in local and referral hospitals. The diagnostic tests, RT-PCR and TR, were analyzed categorically, from the development of 2x2 frequency tables. When analyzing the TR, it was observed that the sensitivity in 2020 was 95% and the specificity 17%; in 2021, the sensitivity was 100% and the specificity 37.5%. The PPV in 2020 was 71% and in 2021, 93%. The VPN in 2020 was 66% and in 2021 100%. It was possible to conclude that the TR proved to be a valid tool to follow up the notification strategy and monitoring of suspected cases in the midst of the COVID-19 Pandemic. Analyses like this could compose dynamic management strategies, as potential sentinel indicators. DOI: https://doi.org/10.56238/colleinternhealthscienv1-021